Play, family involvement, literacy interest and literacy skills among preschoolers from low-income families in Nigeria: sex as a moderator - Mohammed, Nyah; Arshat, Zarinah (Human Resource Management Academic Research Society, 2022)
Previous research reported conflicting findings on the influence of play, family involvement and literacy interest on literacy skills as the influence of these variables varies by sex. Therefore, the present study was conducted to determine the moderating role of sex between these variables among pre-schoolers from low-income families in Taraba State Nigeria. 394 preschool children aged 3 to 5 years with their mothers were selected using a proportionate stratified random sampling technique. The findings confirmed significant direct positive effects of play, family involvement and literacy interest on literacy skills. It also revealed a significant moderating effect of sex on the relationship between play and literacy skills. It also confirmed that the influence of family involvement on literacy skills is moderated by sex. Contrarily, the moderating effect of sex on the relationship between literacy interest and literacy skill was not significant. The study concluded that preschool boys and girls were different in their natural creation which may cause differences in their literacy skills ability. The finding implied the need for more attention from the preschool setting to further improve their academic planning in order to enhance both preschool boys’ and girls’ literacy skills.